Xác định lượng vết Selen bằng phương pháp Von- Ampe hòa tan catot xung vi phân khi có mặt Rh - Trần, Chương Huyến (Đại học Quốc gia Hà Nội, 2017)
A remarkably sensitive cathodic strippmg voltammetric procedure for ultratraee measurements of selenium in the presence of rhodium is described. The metbod is based on the accumulation and subsequent reduction of a Rb2Se3 layer on the hanging mercury drop electrode. Optimised conditions include pH 1.0 to 1.8 (HCl concentration of 10''^ M), 400ppb - 4ppm Rb(III) (depending on the Se(I\0 concentration), and a deposition potential of -0.25V (vs.Ag/AgCl).